Robot Formation Performing a Collaborative Load Transport and Delivery Task by Using Lifting Electromagnets - Oliveira Barcelos, Celso (2023)
Featured Application: Supply delivery tasks are commonly present in hostile regions of natural disasters, in military operations, and in agricultural and urban environments. In this context, the results of this work envision the application of cargo transportation performed by a formation of robots. This paper presents a practical validation of a heterogeneous formation of mobile robots in performing a load lifting, transportation, and delivery task. Assuming that an unmanned ground vehicle (UGV) is unable to perform a mission by itself due to the presence of an obstacle in the navigation route, an unmanned aerial vehicle (UAV) is then assigned to lift the cargo over this UGV, transport the obstacle, and deliver over another UGV. The UAV uses an electromagnetic actuator supported by a cable to pick up the load, the mass of which is 32% of that of the UAV. Experimental results demonstrate that the developed system is capable of performing cargo transport missions and can be scalable for applications such as package delivery in urban or remote areas and supply delivery in conflict or disaster zones.